Fluoride concentrations in industrialized beverages consumed by children in the City of Bauru, Brazil - Lodi, Carolina Simonetti [UNESP]; Ramires, Irene; Pessan, Juliano Pelim [UNESP]; Das Neves, Lucimara Teixeira; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2007)
The increasing consumption of juices, soft drinks and teas among children has increased significantly fluoride ingestion at the age range of risk for development of dental fluorosis. Objective: The purpose of this study was to evaluate fluoride concentrations in some brands of industrialized beverages consumed by children in the city of Bauru, SP, Brazil. Material and Methods: 98 brands of beverages were analyzed, divided into 3 lots, comprising 36, 32 and 30 brands, respectively, for the first, second and third lots. Fluoride concentrations were determined by HMDS-facilitated diffusion, using a fluoride ion-specific electrode (Orion 9409). Results: Fluoride concentrations ranged between 0.04 and 1.76 μg F/mL. It was observed a wide variation in fluoride concentrations among the different brands, as well as the different lots of the same brand. There was no information on fluoride concentrations on the labels of any product. Conclusions: Some of the products analyzed could contribute significantly to the total fluoride intake and, thus, be important risk factors for development of dental fluorosis, which indicates the need of controlling the production of these beverages with respect to fluoride concentration.
Keywords: Beverages; Children; Dental fluorosis; Fluoride